(untitled) (Global Journal of Management and Business Research, 2014)
Mobile telecommunications’ sector is one of the fastest developing sectors in the world. Both high usage and demand gather to show how this sector is increasing especially with the energy resources it requires to operate. Mobile telecommunications has a direct effect on the environment related to the usage (users’ behavior, network’s interaction, power and energy saving, etc.). The main objectives of this research are to assess the consumers’ awareness and willingness to pay in order to go green in mobile telecommunication, while measuring the attitudes, perceived behavioral control, and subjective norms that affect the consumers’ intentions to go green in mobile telecommunications. The theory of planned behavior is used as the conceptual framework to assess the consumers’ intention and behavior towards green telecommunication. A Questionnaire on the theory of planned behavior was built, translated and face to face self-administered interviews were conducted four areas in Lebanon (Jdeideh, Haret Hreik, Roueis, and Maameltein) that were selected based on the traffic profile (voice and data), number of distinct users, locations, population, and workplaces. Results show that most of the Lebanese consumers are aware of the negative environmental and health impacts of telecommunications.